CLEAR - Contact lens wettability, cleaning, disinfection and interactions with tears. Issue 2 (April 2021) - Willcox, Mark; Keir, Nancy; Maseedupally, Vinod; Masoudi, Simin; McDermott, Alison; Mobeen, Rabia; Purslow, Christine; Santodomingo-Rubido, Jacinto; Tavazzi, Silvia; Zeri, Fabrizio; Jones, Lyndon
Abstract: Contact lens materials have undergone significant changes over the past 20 years, particularly with respect to the introduction of silicone hydrogel materials. Whilst this development addressed hypoxic issues, other important areas relating to contact lens success, notably comfort, require further research. Contact lens wettability remains a crucially important part of biocompatibility. Contact lenses can be made more wettable by incorporation of surfactants into blister packs, internal wetting agents, surface treatments or care solutions. However, there remains no clear association between contact lens wettability and comfort, making it challenging to determine the potential for these approaches to be of significant clinical benefit. Most contact lenses are used on a daily wear, reusable basis, which requires them to be disinfected when not worn. The ideal disinfecting solution would also improve comfort during wear. However, balancing these requirements with other factors, including biocompatibility, remains a challenge. Soft lens materials invariably take up and subsequently release certain components of disinfecting solutions onto the ocular surface. This may affect tear film stability and the normal ocular microbiome, and further research is needed in this area to determine whether this has any affect on comfort. Finally, contact lens materials sorb components of the tear film, and these interactions are complex and may change the biochemistry of the tear film, which in turn may affect their comfort. In conclusion, the interaction between lens materials, tear film and disinfection solution plays an important role in the biocompatibility of lenses. However, the exact role and whether this can be altered to improve biocompatibility and comfort during wear remains debatable. This report summarises the best available evidence to examine this complex relationship and the opportunities for practitioners to enhance in-eye comfort of contemporary lenses, along with providing suggestions for areas of study that may provide further information on this topic.